Meningkatkan kemampuan menyajikan data dalam diagram batang melalui penerapan model pembelajaran problem based learning - Retno Suprihatin (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This article contains the result of research conducted on fourth grade elementaryschool students. As for the background of this research is the low ability of fourth gradestudents in presenting data on bar charts. The low ability of students in this material isinfluenced by: (1) students’ ability to solve problems is still low, (2) students often makemistakes in placing the components on bar chart, (3) students are not careful in reading data,and (4) distance learning by giving lots of practice questions makes students confusion. Effortsto improve the ability to present data on bar charts carried out in this study were to apply theproblem based learning, especially about presenting data in bar charts. This research is aclassroom action research. The results of this study indicate an increase in the value of theevaluation results carried out at the end of each cycle. This increase in learning outcomesproves that the problem based learning model is able to improve students’ ability to presentdata on bar charts.